From feeling like rape to a minor inconvenience: Victims' accounts of the impact of computer misuse crime in the United Kingdom. (November 2021) - Button, Mark; Blackbourn, Dean; Sugiura, Lisa; Shepherd, David; Kapend, Richard; Wang, Victoria
Highlights: We conduct the first largescale qualitative research interviewing 52 victims of Computer Misuse Act offences (hacking, malware, ransomware etc) in the United Kingdom. We identify eight broad types of impact that such victims experience. We illustrate impact can be a minor inconvenience but for many the impacts are significant with a small number comparing the impact to serious crimes such as rape. We conclude crimes falling under the Computer Misuse Act should not be treated less seriously just because they are online. Abstract: This paper provides a unique insight into the impact of computer misuse crime, such as hacking, denial of service attacks, ransomware and computer viruses/malware on individual and small and medium sized enterprises/organisation (SME/O) victims in the UK. Based upon in depth interviews with 52 (38 individual and 14 SME/O) victims it shows that these victims experience many of the impacts associated with other volume crimes. Building upon research on comparable offences the paper proposes eight categories of impact, which include:little or no impact, financial, disruption, psychological (which was broken down further), feelings of violation, loss of digital possessions, health and secondary impacts. The research highlights that although for some the impact is very minor, many experience much more extensive impacts, even when there is no financial loss and for some the impact was so severe it was compared to rape.